Melalui Nilai Kepemimpinan Spiritual Membentuk Epistimologi Pendidikan Islam - Jaistyurohman, Robit Azam; Munauwarah, Rahmadin; Sari, Laili Irna; Ghazali, Irwan (ALSYS, 2021)
Islamic education is currently experiencing problems regarding quality and negative cycles. Many studies show that leadership is an influencing factor in an effort to change the negative cycle into a positive one, schools that do not yet have good quality can be turned into quality schools in this case also require support from within Islamic education. In this article, we will discuss spiritual leadership and its significance in improving the quality of education which is currently in decline. In the descriptive analysis method, this article argues that the stagnant education system is partly due to the concept of a purely Western-based education that offers spiritual leadership as an alternative.